The Establishment of a Theoretical Model for the Estimation of Some Photo-Physical Processes in Laser Dyes - Al-Arab, Husam S.; Al-Kadhemy, Mahasin F. H.; Saeed, Asrar Abdulmunem (Iraqi Journal of Science, 2020)
In this study, a new theoretical method for the estimation of absorption and fluorescence spectra is accomplished. These estimations were established following experimental measurements of absorption and fluorescence spectra for the solutions of fluorescein laser dye mixed with titanium dioxide (TiO2) nanoparticlesin distilled water. The used concentration of fluorescein dye was 1x10-5 M, whereas the masses of titanium dioxide nanoparticles were 0.0003g, 0.0005g, 0.001g and 0.002g. An absorption spectra improvement was observed upon raising the mass of TiO2 nanoparticles, which specifies that doping the fluorescein dye with TiO2 nanoparticles have an essential influence on the dye absorption spectra. On the other side, all fluorescence spectra for the dye quenched as TiO2 nanoparticles mass was increased, because of the induced electron transfer. The new method of theoretical estimations was based on curve fitting using Logistic Power Peak (LPP) function to estimate theoretical models for the absorption and fluorescence spectra of thesesamples. The results revealed that these estimated models had exceptional matching shapes with the experimental shapes, so that the estimated models can substitute the experimental measurements.